(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The hospitality sector is undergoing a paradigm transition and has grown significantly since its founding. Rapid industry expansion is expanding the range of job options available to qualified and experienced hospitality professionals. The hospitality and tourist industries have made vital contributions to the economies of the main developing nations. For hotel businesses to be viable and competitive, innovations are absolutely necessary. Industry heavyweights and stakeholders must discover new strategies for growth in order to stay competitive in an increasingly cutthroat climate. Examining and identifying the paradigm shift in the hospitality sector is the aim of this paper. In order to be the greatest service provider, hoteliers are bringing innovations to the hospitality industries, which will also be studied in this article. The research paper also addresses the difficulties the hospitality sector faces in implementing innovations in the sector.